Digital Access among Economics Students: In Terms of Material Access - Joshi, Bishnu Maya (Tribhuvan University Journal, 2023)
The internet and other digital technologies, which provide students access to a prosperity of knowledge and allow them to explore their interests and learn at their own pace, will enable them to do both. The teaching and learning process has grown more effective and meaningful due to ICT's ability to support self-paced learning through various instruments, including assignments, computers, and other devices. Examining the digital divide between economics class 12 students in public and private schools based on access is the main objective of this study. This study used a cross-sectional quantitative survey as its sole data collection method. The researcher used a simple random selection procedure to select 125 respondents from the population as a sample. This study found that private school students have better access than community schools in terms of material access to ICT in school. By giving ICT access in the classroom and persuading parents that it is a fundamental necessity, schools (public and private) can develop highly ICT smartness students in Nepalese.